Poly-β-Hydroxybutyrate (PHB) Production By Amylolytic Micrococcus sp. PG1 Isolated From Soil Polluted Arrowroot Starch Waste - Sebastian Margino; Erni Martani; Andriessa Prameswara (Universitas Gadjah Mada, 2014)
Poly-β-hydroxybutyrate (PHB) production from amylolytic Micrococcus sp. PG1. Poly-β-hydroxybutyrate(PHB) is an organic polymer, which synthesized by many bacteria and serves as internal energy. PHB ispotential as future bioplastic but its price is very expensive due to glucose usage in PHB industry. Thedevelopment of PHB production using starch as an alternative carbon source has been conducted to reducethe dependence of glucose in PHB production. In this study, amylolytic bacteria from arrowroot processingsite were screened quantitavely based on amylase specifi c activity and PHB producing ability. The result of thestudy showed that among of 24 amylolytic isolates, 12 isolates of them were able to accumulate PHB rangedfrom 0,68-11,65% (g PHB/g cdw). The highest PHB production from substrate arrowroot starch was PG1 andafter optimization resulted in increasing of PHB production up to 16,8% (g PHB/g cdw) 40 hours incubationtime. Based on morphological, biochemical and physiological characters, the PG1 isolate was identifi ed asMicrococcus sp. PG1. Result of the FTIR analysis of produced polymer by Micrococcus sp. PG1 was indicatedas poly-β- hydroxybutyrate (PHB)